Pengaruh Metode Latihan Drill terhadap Kemampuan Membaca Mahasiswa Angkatan 2018 Prodi Pendidikan Bahasa Mandarin Universitas Negeri Malang - Dilan Alif Thalita Dzakiyyah; Deddy Kurniawan; Aiga Ventivani (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: Reading ability is one of the essential language skills to learn. The rationale for developing reading ability is because reading constitutes the first step to understanding a lesson. One of the ways to improve reading skills is the drill method. Through the drill method, teachers can instil regular and disciplined students study habits. Applying the drill method in the learning process needs discipline, and teachers play an essential role in its implementation. In other words, the drilling method will not run successfully without teachers' roles. This research aims to describe the impact of the drill approach on students' reading abilities. The research respondents were 38 students of the 2018 Mandarin Language Education Study Program batch, Universitas Negeri Malang. The data is obtained from the pretest-post-test result. Hypothesis testing in this study used an independent sample test. The criteria for testing the hypothesis of the two tests are t-statistic > t-table or if the Sig. (2-tailed) value is less than 0.05; then, there is a significant difference. Or an alternative hypothesis Ha is accepted. The paired samples t-test show that the post-test variance's significance value was 0.18 greater than the pre-test variance value. The significant value of the post-test variance was 0.18 larger than the pre-test variance value, according to the paired samples t-test. According to the data, the possibility of the drill method influencing the pre-test and post-test results is less than 5%. The findings concluded that the drill method might increase students' reading skills. Keywords: drill method, reading ability, Mandarin language. Abstrak: Keterampilan membaca memegang peranan yang penting dalam peningkatan keterampilan kebahasaan. Alasan mengapa pendidik dirasa perlu untuk mengembangkan kemampuan membaca karena membaca merupakan langkah awal untuk memahami suatu pelajaran. Teknik metode drill menjadi bentuk upaya kecil dalam perkembangan kemampuan membaca peserta didik. Metode ini dapat melatih ketangkasan peserta didik untuk menghubungkan sebab-akibat karena aktivitas metode ini yang selalu diulang hingga menyebabkan kemampuan peserta didik semakin meningkat. Keberhasilan penerapan metode drill juga menuntut peran pendidik dalam mendisiplinkan peserta didik karena metode drill tidak akan berjalan sukses tanpa peran pendidik. Penelitian ini bertujuan untuk mendeskripsikan pengaruh penerapan metode drill terhadap kemampuan membaca mahasiswa. 38 mahasiswa pada program pendidikan Bahasa Mandarin angkatan 2018 Universitas Negeri Malang menjadi responden dalam penelitian ini. Data didapatkan dari hasil pre-test post-test. Pengujian hipotesis dalam penelitian ini menggunakan independent sample test. Kriteria pengujian hipotesis dari kedua pengujian adalah t-statistik > t-tabel atau jika nilai Sig. (2-tailed) kurang dari 0,05, maka terdapat perbedaan yang signifikan atau hipotesis alternatif (Ha) diterima. Uji-t sampel berpasangan menunjukkan bahwa nilai signifikansi varians post-test memiliki nilai 0,18 lebih besar dari nilai varians pre-test. Hasil analisis statistik menunjukkan bahwa probabilitas kurang dari 5%, yang berarti bahwa metode drill mempengaruhi hasil pre-test dan post-test. Hasil penelitian menyimpulkan bahwa metode drill dapat meningkatkan kemampuan membaca siswa pada tingkat studi Pendidikan Bahasa Mandarin 2018. Kata Kunci: metode drill, kemampuan membaca, bahasa Mandarin